ANALISIS METODE PEMBERDAYAAN WANITA DI PROPINSI JAWA TIMUR - Nugrahini Susantinah Wisnujati; Siti Rokhmi Fuadati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
Female are citizen who have equal right and obligation with male. Female have huge potency to exert their time and power in domestic, public and social area (department), but in fact female have unequal position with male. Therefore it is necessary to hold female empowerement dealing with social, economic, and cultural condition.Female empowerement often be unsuccesful since the empowerement method is not efficient. The power and precise female empowerement method would support the success of empowerent.